The role of experience, cognition, personality and gender in explaining psychosocial consequences of adolescent gambling - Ricijaš, Neven (2012)
There are a lot of explanations for the development of problem gambling. Theoretical models emphasize the importance that different emotional, motivational, cognitive, behavioral and personality factors have for the development of problems related to gambling. Our aim was to explore the strength that experiences with gambling activities, specific motivation for gambling, ways people think about gambling, and broad personality dimensions have in explaining psychosocial consequences of adolescent gambling. We were also interested in whether these factors explain boys’ and girls’ gambling in the same way. A representative sample of 1.952 high-school students (53% girls ; 47% boys) from four major Croatian cities (regional centers) participated in the study. Age varied from 14 y. (first grade) to 20 y. (fourth and final year), with mean age M=16, 56 (SD=1, 17). Canadian Adolescent Gambling Inventory (CAGI) was used to assess the full spectrum of risks and harms associated with gambling in the general youth population. We also asked about participant’s experiences with gambling, their motivation for gambling, and we administered the Beliefs about Gambling Activities Scale and a big five personality measure (IPIP 50). Results emphasize the importance of gaining a large amount of money through gambling activities and chasing (as a model of behavior) for the prediction of problem gambling. Motivational and cognitive factors are also important predictors, with slightly different patterns of results for boys and girls. Broad personality dimensions do not seem to play a role in explaining problem gambling in either gender. Practical contributions of the findings are also discussed.